ATTITUDE OF WOMEN OF NWFP TOWARDS ANTENATAL CARE - Sultana, Anwar; Ahmed, Shafiq (Journal of Ayub Medical College Abbottabad, 2002)
Background: A safe motherhood initiative is a global effort to reduce maternal mortality and morbidity. This aims to ensure improvement in the quality and safety of lives of women through adoption of health and non-health strategies. Antenatal care is a branch of preventive medicine dealing with prevention and early detection of pregnancy disorders. It is the key to modern obstetrics. Methods: It was a descriptive type of study to find out the attitude of the women towards utilization of antenatal care facility at a newly commissioned hospital, Hayatabad Medical Complex, Peshawar, Pakistan in the first year of its working. Results: We recorded 980 patients. All of them were married. Monthly attendance showed increasing trend. In this study 72.44% of the women were of 25-35 year of age while 11.42% were teenager. Multiparity was recorded in 38.97% and 12.14% had more then nine pregnancies. Six hundred and fifty patients were living near the hospital. 2.24% patients visited more than six times and 63.26% had one visit only, with the rest visiting for 2-5 times. Thirty patients had medical disorders. Obstetrical diseases were detected in 194 patients. Pregnancy losses contributed to 146 women and 3 women had more then 6 losses. 254 women selected hospital delivery. Out of then 160 women were booked in the 3rd trimester. Caesarean section rate among those women was 16.4%. Conclusions: The conclusion drawn was that the women living near the hospital used the facility. Antenatal care should be provided to the women at the doorstep of their house. There is a system of lady health workers that should be expanded to cover all areas. Basic health units must be fully equipped and staffed. Communication system should be improved. There is a need to include health education in the curricula of primary education.